تقييم لطاخة عنق الرحم وتنظير عنق الرحم المكبر عند الحوامل في الأشهر الثلاثة الأولى من الحمل - سلمان, صفاء; أحمد, عيسى; جلعود, رائدة (Latakia University Journal -Medical Sciences Series, 2014)
أجري البحث في قسم التوليد وأمراض النساء في مشفى الأسد الجامعي في اللاذقية، في الفترة الواقعة بين 5/1/2012، و1/8/ 2013، شمل البحث150 سيدة، إذ تم تقسيم العينة المدروسة إلى 100 سيدة حامل و50 سيدة غير حامل. تبين بالدراسة أن نسبة حساسية اللطاخة في الحمل هي100 % ونوعيتها هي 76.74%، ونسبة التوافق مع التشخيص النسيجي النهائي 79.38%. بينما بلغت نسبة حساسية التنظير90.91% ونوعيته 76.74%، كما بلغت نسبة التوافق مع التشخيص النسيجي النهائي 78.35%. وهكذا نستنتج أن كلاً من اللطاخة والتنظير المكبر لعنق الرحم وسيلتا مسح جيدتان وآمنتان ، يمكن الاعتماد عليهما في الاستقصاء الأولي عن الآفات السرطانية وما قبل السرطانية خلال فترة الحمل. This research was carried out in the Department of Obstetrics and Gynecology in Alassad Hospital of Tishreen University in Lattakia in the period between 5th of Jan 2012 to 1st of Aug 2013. The sample tested was divided into two groups: 100 pregnant women, and 50 not pregnant. The study showed that the ratio of the sensitivity of Pap test in pregnancy was 100%, and its quality was 76.74%. The Compatibility with overall histological diagnosis was 79.38%. However, the ratio of the sensitivity of Colposcopy was 90.91% and its quality was 76.74%. The Compatibility with overall histological diagnosis was 78.35%. Thus we conclude that both Pap Smear and colposcopy are safe and good scanning tools. They can be used in the preliminary prognosis for carcinomatous and precarcinomatous tumors through the duration of pregnancy.